Gender Bias Analysis And Right To Fight For Gender Equality In Education Through The Children's Book “I Am Kartini” - Ulfa, Faiza; Mukaromah, Nisaul; Puspitasari, Dewi (Faculty of Social and Political Sciences University of Bangka Belitung, 2023)
This study employs visual discourse analysis to reveal the visual elements within the children's book